Phosphoregulation of the human SMN complex - Husedzinovic, Alma; Oppermann, Felix Sebastian; Dräger-Meurer, Stefanie; Chari, Ashwin; Fischer, Utz; Daub, Henrik; Gruss, Oliver (European journal of cell biology, 2014)
The survival motor neuron (SMN) complex is a macromolecular machine comprising 9 core proteins: SMN, Gemins2-8 and unrip in vertebrates. It performs tasks in RNA metabolism including the cytoplasmic assembly of spliceosomal small nuclear ribonucleoprotein particles (snRNPs). The SMN complex also localizes to the nucleus, where it accumulates in Cajal Bodies (CB) and may function in transcription and/or pre-mRNA splicing. The SMN complex is subject to extensive phosphorylation. Detailed understanding of SMN complex regulation necessitates a comprehensive analysis of these post-translational modifications. Here, we report on the first comprehensive phosphoproteome analysis of the intact human SMN complex, which identify 48 serine/threonine phosphosites in the complex. We find that 7 out of 9 SMN components of the intact complex are phosphoproteins and confidently place 29 phosphorylation sites, 12 of them in SMN itself. By the generation of multi non-phosphorylatable or phosphomimetic variants of SMN, respectively, we address to which extent phosphorylation regulates SMN complex function and localization. Both phosphomimetic and non-phosphorylatable variants assemble into intact SMN complexes and can compensate the loss of endogenous SMN in snRNP assembly at least to some extent. However, they partially or completely fail to target to nuclear Cajal bodies. Moreover, using a mutant of SMN, which cannot be phosphorylated on previously reported tyrosine residues, we provide first evidence that this PTM regulates SMN localization and nuclear accumulation. Our data suggest complex regulatory cues mediated by phosphorylation of serine/threonine and tyrosine residues, which control the subcellular localization of the SMN complex and its accumulation in nuclear CB.
Gesehen am 12.08.2020